HUBUNGAN ANTARA KETEKUNAN (PERSISTENCE) DENGAN HASIL BELAJAR BIOLOGI: STUDI KORELASIONAL TERHADAP SISWA KELAS X MIA DI SMA NEGERI 102 JAKARTA - Miarsyah, Mieke; Putrawan, I Made; Hermadianti, Dea (Universitas Negeri Jakarta, 2016)
Persistence refers to the length of time a person sticks with a given action. This can be seen from staying power of behavior or how long a person will continue to devote effort. The purpose of this research was to determained the relationship between persistence with biology learning outcomes of students of Sains grade X on ecosystem material. The research was accomplished at 102 Senior High School of Jakarta in April-May 2016. The method of this research used survey method through correlational study. The subject of this research were students of Sains grade X with sample of 75 students were selected by simple random sampling. Results of the normality data tested by Kolmogorov Smirnov test, resulting that two data population normality distributed. Data homogenity tested by Bartlett test resulting data obtained from the two homogeneous variable. Hypothesis test using regression test, found that the regression model Å¶ = 2.547 + 0.208X had a significant and linier relationship. The result of Pearson Product Moment test was correlation value obtained 0.87. The calculation of the determination coefficient obtained 0.7569. It was that 75.69% of persistence contributed to the biology learning outcomes on ecosystem material while 24.31% was determined by other factors.